2021
DOI: 10.3390/nu13030805
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Fatty Acids Profile in Kidney Transplant Recipients

Abstract: Patients with end-stage kidney disease, treated with renal transplantation, are at increased risk of cardio-vascular disease (CVD) and cardio-vascular mortality. They are also characterized by an atherogenic dyslipidemia. Alterations of the fatty acids (FA) profile contribute to increased cardio-vascular risk in the general population. In the current study, we test the hypothesis that kidney transplantation is associated with ab-normalities in FA profile. The FA profile was analyzed by gas chromatography–mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
(43 reference statements)
0
8
2
Order By: Relevance
“…The many metabolic changes [41] and slow recovery post-surgery in patients with CKD may also contribute to the deviation in the FA profile observed in our previous study. Therefore, the results of the current study are expectedly different from the previous study [20]. Even though the duration of the current study was relatively short, the alteration of the FA profile was significant.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…The many metabolic changes [41] and slow recovery post-surgery in patients with CKD may also contribute to the deviation in the FA profile observed in our previous study. Therefore, the results of the current study are expectedly different from the previous study [20]. Even though the duration of the current study was relatively short, the alteration of the FA profile was significant.…”
Section: Discussioncontrasting
confidence: 87%
“…In our previous studies, we observed that despite normal kidney function after transplantation, the FA profile was still abnormal [19]. Our recent work concerning a comparison of FA profiles in patients at different time intervals after transplantation and healthy controls showed many differences in FA profiles [20]. In that study, however, we were unable to evaluate the same patients before and after transplantation, as we did in this study.…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations